2015
DOI: 10.1109/jsen.2015.2397874
|View full text |Cite
|
Sign up to set email alerts
|

CMOS Image Sensor With Area-Efficient Block-Based Compressive Sensing

Abstract: We have designed, fabricated and measured the performance of a linear and area-efficient implementation of the compressive sensing (CS) method in CMOS (complementary metal-oxide-semiconductor) image sensors. The use of an active pixel sensor (APS) with an integrator and in-pixel current switches are exploited to develop a compact implementation of CS encoding in analog domain. The intrinsic linearity of APS with integrator circuit guarantees the linearity of the CS encoding structure. The CS measurement proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Content may change prior to final publication. [15]. Inside of each pixel, the flip-flops are replaced by simple and more compact selectors.…”
Section: Rip Of Binary Matrices Produced By Pseudo Random Binary mentioning
confidence: 99%
See 1 more Smart Citation
“…Content may change prior to final publication. [15]. Inside of each pixel, the flip-flops are replaced by simple and more compact selectors.…”
Section: Rip Of Binary Matrices Produced By Pseudo Random Binary mentioning
confidence: 99%
“…If each pixel received two driving signals, it would be possible to use one of them to determine if the pixel took part in a compressed sample and, in case it did, use the other to select the sign of its contribution. Since recent CS-CIS examples [6][14] [15] have shown that as few as = 2√ bits of information are needed to generate binary measurement matrices on-chip, the amount of resources (number of transistors) needed to incorporate a ternary matrix would still be implementable in a CS-CIS design. Each coefficient of the resulting matrix would have a probability distribution of:…”
Section: Ternary Matrices Generated Using Class III Elementary Cmentioning
confidence: 99%
“…Noting that data reduction during the CS measurement does not completely equal to signal compression yet, though these measurements can be transmitted directly [5,6], a large bandwidth is still needed. To further reduce load of the transmitter, CS-CIS needs to be cooperated with a compressor to generate a compressed bitstream.…”
Section: Introductionmentioning
confidence: 99%
“…So, column level ADC should be small in size. In CIS a scene is focused by a lens through an array of pixels on to image sensor which converts light into electrical signal [6]. Each pixel consists of one photodiode to sense the light and some transistor.…”
Section: Introductionmentioning
confidence: 99%